2003
DOI: 10.1046/j.1524-4741.2003.09308.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Screening Mammography on the Comparative Survival Rates of African American, White, and Hispanic Beneficiaries of a Comprehensive Health Care System

Abstract: This study reviewed mammographic screening related to breast carcinoma diagnosis and treatment between 1987 and 1997 at Brooke Army Medical Center, San Antonio, TX. Epidemiologic data from the Department of Defense Automated Central Tumor Registry were merged with data from patients' medical records and responses of the patients or their families to a mailed survey. The cases of 907 women grouped by race-white, African American, and Hispanic-were analyzed. Breast carcinoma diagnosed by mammographic screening s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…While we were unable to assess mammography usage in this population, results from prior studies suggest that it would be unlikely to significantly change the results [70,71]. Early detection may not be as useful for high grade, rapidly growing tumors, of which there are an excess in African American and Hispanic women due to the association between young age and high-risk tumors.…”
Section: Discussionmentioning
confidence: 82%
“…While we were unable to assess mammography usage in this population, results from prior studies suggest that it would be unlikely to significantly change the results [70,71]. Early detection may not be as useful for high grade, rapidly growing tumors, of which there are an excess in African American and Hispanic women due to the association between young age and high-risk tumors.…”
Section: Discussionmentioning
confidence: 82%
“…Survival trends for women with breast cancer have slowly improved over the past several decades [1], although disparities by race remain, with the majority of reports showing better survival for Caucasian compared with AA women [2][3][4][5][6][7][8][9][10][11][12][13]. An important question regarding racial differences in breast cancer survival pertains to the degree in which these differences are due to inherent biologic and/or genetic differences, social economic factors, and/or factors related to the quality of medical care received.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous population-based studies using data from the Surveillance, Epidemiology and End Results (SEER) program [2][3][4][5][6][7][8][9][10] and other data bases [11][12][13], have been published showing worse prognostic features and lower survival rates for AA and other ethnic minority women with breast cancer compared with Caucasian women. A number of studies have also reported on racial differences in the patterns of care for women with breast cancer [8][9][10][11][12]14]. Unequal access to state-of-the-art cancer-directed treatment might, in part, explain racial differences in survival among women with breast cancer in this country.…”
Section: Introductionmentioning
confidence: 99%
“…These disparities are mediated by many factors that promote and create barriers to screening and treatment, including socioeconomic characteristics, cultural beliefs, and health insurance status [12][13][14][15][16][17][18][19]. However, even in comprehensive, equal-access health care systems where access to screening and care is the same, Hispanic women are more likely to present with more advanced stage disease, at younger ages and with larger tumors than Caucasian women [20][21][22].Receipt of optimal breast cancer treatment has also been shown to differ between Hispanic and non-Hispanic white women. Even though the recommended care for most women with stage I or II breast cancer is breast-conserving surgery (BCS) with radiation or mastectomy [23], Hispanic women in the US have lower rates of BCS with radiation…”
mentioning
confidence: 99%